Soluble endoglin and hypercholesterolemia aggravate endothelial and vessel wall dysfunction in mouse aorta - Vitverova, Barbora; Blazickova, Katerina; Najmanova, Iveta; Vicen, Matej; Hyšpler, Radek; Dolezelova, Eva; Nemeckova, Ivana; Tebbens, Jurjen Duintjer; Bernabeu, Carmelo; Pericacho, Miguel; Nachtigal, Petr (Atherosclerosis, 2018)
BACKGROUND AND AIMS: Increased plasma levels of soluble endoglin (sEng) were detected in patients with endothelial dysfunction-related disorders and hypercholesterolemia. In this study, we hypothesized that high levels of sEng accompanied by mild hypercholesterolemia could aggravate endothelial and vessel wall dysfunction and affect endoglin/eNOS signaling in mouse aorta. METHODS: Three-month-old female transgenic mice on CBAxC57BL/6J background, with high levels of sEng (Sol-Eng+high HFD), and their littermates with low levels of sEng (Sol-Eng+low HFD), were fed a high fat diet for six months. Plasma samples were used for biochemical, ELISA and Luminex analyses of total cholesterol, sEng and inflammatory markers. Functional parameters of aorta were assessed with wire myograph 620M. Western blot analyses of membrane endoglin/eNOS signaling and endothelial dysfunction/inflammation markers in aorta were performed. RESULTS: Functional analysis of aorta showed impaired KCl induced vasoconstriction, endothelial-dependent relaxation after the administration of acetylcholine as well as endothelial-independent relaxation induced by sodium nitroprusside in the Sol-Eng+high HFD group compared to the Sol-Eng+low HFD group. Ach-induced vasodilation after administration of l-NAME was significantly higher in the Sol-Eng+high HFD group compared to the Sol-Eng+low HFD group. The expression of endoglin, p-eNOS/eNOS, pSmad2/3/Smad2/3 signaling pathway was significantly lower in the Sol-Eng+high HFD group compared to the Sol-Eng+low HFD group. CONCLUSIONS: The results indicate that long-term hypercholesterolemia combined with high levels of sEng leads to the aggravation of endothelial and vessel wall dysfunction in aorta, with possible alterations of the membrane endoglin/eNOS signaling, suggesting that high levels of soluble endoglin might be considered as a risk factor of cardiovascular diseases.
Keywords: signální transdukce; aorta; protein Smad3; nemoci aorty; upregulace; vazodilatace; Phosphorylation; Signal Transduction; Smad2 Protein; Smad3 Protein; Humans; Up-Regulation; endoglin; Endothelium, Vascular; Mice, Transgenic; Vasodilation; fosforylace; cévní endotel; Endoglin; Diet, High-Fat; protein Smad2; Female; myši transgenní; ateroskleróza; lidé; zvířata; myši inbrední C57BL; vazokonstrikce; Mice, Inbred CBA; ženské pohlaví; Aortic Diseases; Atherosclerosis; Mice, Inbred C57BL; hypercholesterolemie; synthasa oxidu dusnatého, typ III; Hypercholesterolemia; dieta s vysokým obsahem tuků; Animals; myši inbrední CBA; Inflammation Mediators; Aorta; Nitric Oxide Synthase Type III; Disease Models, Animal; mediátory zánětu; Vasoconstriction; modely nemocí na zvířatech